A critical comparison of different approaches to sediment-quality assessments in the Santos estuarine system in Brazil - Torres, Ronaldo José; Cesar, Augusto; Almagro Pastor, Victor; Pereira, Camilo Dias Seabra; Choueri, Rodrigo Brasil; Cortez, Fernando Sanzi; Morais, Rodofley Davino; Abessa, Denis Moledo de Souza [UNESP]; Nascimento, Marcos Roberto Lopes do; Morais, Cassia Rodrigues de; Fadini, Pedro Sergio; Del Valls Casillas, Tomas Angel; et al. (Springer, 2015)
This study focuses on the discussion of different lines of evidence (LoEs) applied to a sediment-quality assessment that considered the following: chemical concentrations of metals; polycyclic aromatic hydrocarbons (PAHs) in estuarine waters, sediments, and oysters (native and caged Crassostrea brasiliana); PAHs in semipermeable membrane devices (SPMDs); simultaneously extracted metals-acid volatile sulfides (SEM-AVS); benthic community assessment (the exploratory benthic index and the relative benthic index); chronic toxicity tests with the sea urchin Lytechinus variegatus; and bioaccumulation models. Significantly contaminated sediments from the Santos Estuarine System and the consequent toxicity of tested organisms were measured. Caged oysters presented bioaccumulation rates a parts per thousand currency sign2,500 % of total PAH content and 200 % of metal content when compared with control organisms from an uncontaminated area. SPMD results presented the same bioaccumulation pattern as caged oysters but at lower concentrations. Benthic communities presented some alterations, and there was a predominance of tolerant species in the inner part of the estuary. According to the SEM-AVS approach, metals should be assumed to be nonbioavailable, but experiments with transplanted C. brasiliana showed metal bioaccumulation, particularly in the cases of chromium, copper, mercury, and zinc. The weight-of-evidence approach was applied to compare and harmonize LoEs commonly used in sediment-quality assessments and to then classify estuary environments according to both their potential for having adverse effects on the biota and their possible ecological risks. All of the results of these approaches (except for SEM-AVS) were found to complement each other.